A comparison of spent resin degradation by Fenton and O3-Fenton process. (December 2020) - Feng, Wendong; Li, Jian; Gao, Kai; An, Hongxiang; Wang, Yunhai
Abstract: The treatment of spent resin generated by nuclear power plants using Fenton and O3 -Fenton process as an alternative to the present cementation method is an attractive solution. A comparison among O3 -Fenton and Fenton process for spent resin degradation were performed in this investigation. The different effects of reaction temperature and ozone concentration was compared between Fenton and O3 -Fenton process. In addition the resulted COD removal ratio, residue weight, iron ions concentration change, resin dissolution, degradation intermediates and final products were also compared in these two processes. The results showed that the addition of O3 to Fenton process can improve the degradation ratio of spent resin. With an O3 concentration of 161.3 mg/L, the resin degradation ratio reached 97.1%. The residue COD of O3 -Fenton process was 60.0% lower than Fenton process. With O3 addition, the dissolution rate of spent resin was reduced and the mineralization rate of dissolved organics increased by 19.3%. The residual organic matters in the final solution included mainly oxalic acid. The degradation of spent resin after dissolution conformed to the first-order kinetic equation in both Fenton and O3 -Fenton process. O3 -Fenton process could get better results and save processing costs. Graphical abstract: Image 1 Highlights: The mineralization rate of dissolved organics increased with O3 addition. The main oxidized products in the residual solution was small molecular acids. The resin degradation conformed to the first-order kinetic equation. The O3 -Fenton process could get better results and save processing cost.